Separation of Bovine Serum Albumin Using Chromatographical Column: Parameters and Simulation - Khoshaba Haweel, Cecilia; J. Ali, Ahmed; N. Alias, Samar (Iraqi Journal of Chemical and Petroleum Engineering, 2010)
A liquid-solid chromatography of Bovine Serum Albumin (BSA) on (diethylaminoethyl-cellulose) DEAE-cellulose adsorbent is worked experimentally, to study the effect of changing the influent concentration of (0.125, 0.25, 0.5, and 1 mg/ml) at constant volumetric flow rate Q=1ml/min. And the effect of changing the volumetric flow rate (1, 3, 5, and 10 ml/min) at constant influent concentration of Co=0.125mg/ml. By using a glass column of (1.5cm) I.D and (50cm) length, packed with adsorbent of DEAE-cellulose of height (7cm). The influent is introduced in to the column using peristaltic pump and the effluent concentration is investigated using UV-spectrophotometer at 30oC and 280nm wavelength. A spread (steeper) break-through curve is gained at lean feed concentration of 0.125mg/ml, while the flow rate greater than (3ml/min) is almost the same. So it is butter to work at low volumetric flow rate between (1-3) ml/min. The equilibrium-dispersion model of liquid-solid chromatography for a binary mixture, related with Langmuir isotherm correlation is used in the modeling of this work. The resulting model is solved numerically by using MATLAB V.6.5 program.